International bank crisis management : a transatlantic perspective - Bodellini, Marco (Oxford : Hart Publishing, 2022)
"This book analyses the legal regimes governing bank crisis management in the EU, UK, and US, discussing the different procedures and tools available as well as the regulatory architecture and the authorities involved. Building on a broad working definition of 'bank crisis management' and referring to several cases, the book explores the techniques and approaches employed by the authorities to deal with troubled banks on both sides of the Atlantic. The legal analysis distinguishes between procedures and tools aimed at liquidating the bank in crisis vis-à-vis those aimed at restructuring. In this regard, attention is paid to the rules allowing for the use of public money in handling banks in trouble as well as to the role that deposit insurance schemes can play. Considerations on the impact on banks of the current crisis provoked by the COVID-19 pandemic are advanced, primarily focusing on the expected surge of non-performing loans as well as on ways to effectively manage these assets. The book approaches these issues from a comparative law perspective, providing law and economics considerations and focusing on strengths and drawbacks of the rules currently in force. The book advances policy considerations as well as reform proposals aiming at enhancing the legal regimes in force, with particular reference to the Consultation promoted in 2021 by the European Commission on the adoption of a new bank crisis management and deposit insurance framework in the Union."--
5. The Crisis of Systemic Institutions: Resolution and Orderly Liquidation Authority : I. Introduction ; II. Resolution in the EU ; III. The Resolution Tools ; IV. Bail-in ; V. Resolution Funds ; VI. The Provision of Public Funds in the Context of Resolution and the Interaction between the Resolution Regime and the State Aid Framework ; VII. Impediments to Resolvability ; VIII. Resolution within the Banking Union ; IX. The UK Regime ; X. The US Regime: The Orderly Liquidation Authority ; XI. Concluding Remarks -- 6. Deposit Guarantee Schemes : I. Introduction ; II. The Functions Performed by Deposit Guarantee Schemes in Bank Crises ; III. The Interplay between the Legislation on DGSs and the State Aid Regime ; IV. The Key Contributions of DGSs in Handling Bank Crises ; V. The General Court of the European Union and the Court of Justice of the European Union Judgments in the Banca Tercas Case ; VI. The Current Legal Constraints to DGSs' Optional Interventions in Bank Crises ; VII. Deposit Insurance in the US ; VIII. A Limited-Scope Reform Proposal to Allow DGSs to Play a Leading Role in Bank Crises -- 7. The Legacy of the COVID-19 Crisis: The Non-Performing Loan Problem : I. Introduction ; II. Non-Performing Loans ; III. How to Tackle the Non-Performing Loan Problem: Asset Management Companies ; IV. Types of NPLs to Transfer ; V. Transfer Price ; VI. Capital and Funding Structure and Governance Arrangements ; VII. Concluding Remarks -- 8. Conclusions.
Includes bibliographical references and index.
Also issued in print: Hart Publishing, 2022. Digital resource published 2022.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Description based on online resource; title from digital title page (viewed on September 29th, 2022).
Keywords: Banks and banking, International -- Management; Financial crises; Banking law; Comparative law; United Kingdom; Great Britain; USA; EU (European Union); Electronic books